MENINGKATKAN MOTIVASI BELAJAR SISWA SMA MENGGUNAKAN MEDIA BELAJAR INSTRUCTIONAL GAMES - Fauzi Faisal Nugraha; Eryan Ahmad Firdaus (Yayasan Grace Berkat Anugerah, 2024)
Games that are interesting and fun to play make the interest of students to prefer playing games rather than studying. Submission of teaching materials in a conventional way will be boring to be followed by students in class. It is necessary to improve teaching methods that are able to attract students' interest in learning to be motivated in participating in teaching and learning activities. The design of interactive learning media with the instructional games model aims to increase the interest of students so that they can receive teaching materials in a good and fun way. The method used in this research is Research and Development (R&D). To analyze students' learning motivation, a field survey questionnaire was used which was given to 33 students of Class XI SMA Negeri 1 Plered. There has been an increase of 8.22%, where the initial motivation of students is at the percentage of 62.88% increasing to a percentage of 71.10%, which can also be interpreted that the use of interactive instructional games learning media is able to increase student learning motivation.